(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
In recent years, there have been many difficulties in the teaching-learning of mathematics, before this arises the need to seek innovative teaching-learning practices that place the student at the center of the educational process. Project-Based Learning (PBL) is an active methodology that facilitates teacher-student interaction and achieves significant learning. The objective of this work is to determine the incidence of PBL and its application in location measures at the basic level. The applied methodology describes an exploratory-descriptive quantitative investigation. The results indicate a considerable difference before and after the application of the ABP.